Optimalisasi Diagnosis Pemahaman Konsep Alternatif Melalui Multi-Tier untuk Analisis Laju Reaksi - Siregar, Fitriyuni Miralda; Rahmawati, Yuli; Irwanto, Irwanto (LPPM Universitas Negeri Jakarta, 2024)
This study aims to investigate the understanding of reaction kinetics in grade 11 students. The study used a multi-tiered diagnostic instrument to analyze the level of understanding and alternative concepts in 139 students. The results showed that understanding reaction kinetics was a difficult topic for grade 11 students, with a total of 107 alternative concepts revealed. As many as 63% of questions that display graphs obtain significant alternative concepts. Overall, the multi-tier format for the diagnostic instrument shows excellent utility for investigating students' understanding and uncovering students' alternative concepts on reaction kinetics. Confidence in answering questions also provides further information about how students perform on tests and classifies these alternative concepts.